2003
DOI: 10.1002/bsl.559
|View full text |Cite
|
Sign up to set email alerts
|

Opinion formation in evaluating sanity at the time of the offense: an examination of 5175 pre‐trial evaluations

Abstract: Sanity evaluations are high-stake undertakings that explicitly examine the defendant's culpability for a crime and implicitly explore clinical information that might inform a plea agreement. Despite the gravity of such evaluations, relatively little research has investigated the process by which evaluators form their psycholegal opinions. In the current study, we explore this process by examining 5175 sanity evaluations conducted by a cohort of forensic evaluators in Virginia over a ten-year period. Our analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
97
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(111 citation statements)
references
References 25 publications
12
97
2
Order By: Relevance
“…Clinical variables accounted for more than 20% of the variance in the evaluation outcome and, when the demographic and crime variables were added into the predictive model, they increased the variance explained by the outcome model by about only 1% per additional variable. Similar results have emerged in recent studies concerning both adjudicative competence and legal sanity (Cochrane et al, 2001;Warren, Murrie, Chauhan, Dietz, & Morris, 2004). Apparently seriously mentally ill defendants more often face charges for less serious, public nuisance, crimes.…”
Section: Discussionsupporting
confidence: 72%
“…Clinical variables accounted for more than 20% of the variance in the evaluation outcome and, when the demographic and crime variables were added into the predictive model, they increased the variance explained by the outcome model by about only 1% per additional variable. Similar results have emerged in recent studies concerning both adjudicative competence and legal sanity (Cochrane et al, 2001;Warren, Murrie, Chauhan, Dietz, & Morris, 2004). Apparently seriously mentally ill defendants more often face charges for less serious, public nuisance, crimes.…”
Section: Discussionsupporting
confidence: 72%
“…Additionally, Warren et al (2004) found a negative relation between Axis II personality disorders and opinions supportive of insanity: subjects with a personality disorder were less likely to be found insane than subjects without a personality disorder. In contrast, Janofsky, Dunn, Roskes, Briskin, & Rudolph (1996) did not find any relationship between diagnosis and verdicts of insanity.…”
Section: Introductionmentioning
confidence: 90%
“…The few empirical studies that have addressed factors involved in assessing criminal responsibility consistently show that experts' opinions regarding criminal responsibility and verdicts of insanity are related to Axis I psychiatric diagnoses; notably, subjects with psychotic disorders were more likely to be found insane than subjects without psychotic symptoms (Lymburner & Roesch, 1999;Warren, Murrie, Chauhan, Dietz, & Morris, 2004;Rice & Harris, 1990;Cochrane, Grisso, & Frederick, 2001). Additionally, Warren et al (2004) found a negative relation between Axis II personality disorders and opinions supportive of insanity: subjects with a personality disorder were less likely to be found insane than subjects without a personality disorder.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…NGRI acquittees tend to have a diagnosis of psychosis and not personality disorder (Rice & Harris, 1990). Between 60 and 77% of all NGRI acquittees are diagnosed with a psychosis and at least 10% of these individuals have a diagnosis of organic psychosis, indicating a possible biological origin to their disorder (Cochrane, Grisso, & Frederick, 2001;Roberts et al, 1987;Warren, Murrie, Chauhan, Dietz, & Morris, 2004). In contrast, a diagnosis of a personality disorder appears to impede a successful NGRI verdict: only 9-19% of those who are successful while pleading NGRI are diagnosed with a personality disorder (Rogers & Zimbarg, 1987;Zonana, Wells, Getz, & Buchanan, 1990).…”
Section: How Jurors Perceive Scientific Evidencementioning
confidence: 98%